Hipnoterapi Untuk Mengurangi Nyeri Kala I - Umi Marifah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: to identify the effectiveness of hypnotherapy in reducing pain in the first period of laborMethods: This study used an analytical observational design with a cross-sectional approach. This research was conducted in September 2021. The number of samples in this study was 30 respondents. The samples in this study were all maternity mothers who came to PKU Muhammadiyah Hospital Surabaya. The sampling technique used purposive sampling. Data analysis is carried out by using the statistic test Mann-Whitney. Results: the results of the statistical test showed that the p-value of 0.000 was smaller than the value of Î± = 0.05 so there was hypnobirthing effective in reducing pain in childbirth during the first periodConclusion: The results of this study found that hypnobirthing is effective in reducing labor pain